2016
DOI: 10.1155/2016/7157039
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of Endocan in Patients with Meningiomas and Gliomas

Abstract: Objective. Endocan has been shown to be a marker for several cancers and may show degree of malignancy. The aim of this study is to assess tissue levels of endocan in common brain tumors, namely, meningiomas, low-grade gliomas (LGGs), and high-grade gliomas (HGGs). Patients and Methods. Endocan was assayed by commercially available enzyme linked immunosorbent assay (ELISA) kits in a total of 50 brain tumors (20 meningiomas, 19 LGGs, and 20 HGGs) and 15 controls. The results were compared to control brain tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…They found that the mean level of endocan has a significant incline from the control group to the malignant tumor groups although the meningioma (benign) had the lowest mean level, and the high-grade glioma (most malignant) group had the highest mean level. They also showed that incline expression was significantly correlated with the degree of malignancy, which means that with increasing the degree of malignancy, the endocan expression also increased [26]. In another study, Maurage and colleagues investigated endocan expression in brain tumors.…”
Section: Discussionmentioning
confidence: 98%
“…They found that the mean level of endocan has a significant incline from the control group to the malignant tumor groups although the meningioma (benign) had the lowest mean level, and the high-grade glioma (most malignant) group had the highest mean level. They also showed that incline expression was significantly correlated with the degree of malignancy, which means that with increasing the degree of malignancy, the endocan expression also increased [26]. In another study, Maurage and colleagues investigated endocan expression in brain tumors.…”
Section: Discussionmentioning
confidence: 98%
“…According to the published work on meningioma and glioma, endocan expression showed a steady incline from the controls to the most malignant form of the tumor groups. The authors suggested a positive correlation between the endocan expression level and the degree of malignancy (38). These findings may confirm the role of endocan in cancer cell differentiation.…”
Section: Discussionmentioning
confidence: 54%
“…Endocan, the endothelial cell speci c molecule-1 (ESM-1), was demonstrated to be associated with angiogenesis and tumor growth in lung, kidney and liver among other cancers (10)(11)(12). Moreover, endocan expression was correlated with high grade gliomas (13,14). It has been proposed as a neovascularization marker, being stimulated by two other important angiogenic factors VEGF and broblast growth factor (FGF2) (10,13), and, importantly, it is involved in the switch from dormant to fast growing and angiogenic tumors (15).…”
Section: Read Full License Introductionmentioning
confidence: 99%